Recent advances of noble metal aerogels in biosensing. Issue 3 (11th February 2021) - Gao, Wei; Wen, Dan
Abstract: Noble metal aerogels were first reported in the late 2000s and developed rapidly over the past 10 years. With the structure advantages of ultralow density, high porosity, large specific surface area and hierarchical structure like traditional aerogels, noble metal aerogels with good conductivity and specific chemical properties have attracted great research interests and application potentials in various fields, including biological applications. Here, in this perspective, recent advances about the preparation and application of noble metal aerogels in biosensing are summarized and highlighted. As mimics of bio‐active "nanozymes" and as supports of natural enzymes, noble metal aerogel‐based biological sensors exhibited much better activity and sensitivity towards the detection of various substrates compared to their counterparts of nanostructured materials. Moreover, the main challenges and perspectives of noble metal aerogels about their biocompatibility, types, surface properties, selectivity, and potential in wearable applications for biosensing are also emphasized and addressed. Overall, as a novel branch of aerogels, noble metal aerogels hold great promises for biological sensing applications and still have many problems to overcome for better utilizations. Abstract : The special structural features and chemical properties allowed noble metal aerogels as excellent platforms for biological sensing of various biomolecules. In this perspective, the developments and applications in biosensing for noble metal aerogels are generally summarized to shed light on their advantages and advances. Challenges and perspectives on the future of noble metal aerogels in biosensing are also proposed.